AKR1B10-inhibitory Selaginella tamariscina extract and amentoflavone decrease the growth of A549 human lung cancer cells in vitro and in vivo. (18th April 2017) - Jung, Yu-Jin; Lee, Eun Ha; Lee, Chang Gun; Rhee, Ki-Jong; Jung, Woo-Suk; Choi, Yongsoo; Pan, Cheol-Ho; Kang, Kyungsu
Abstract: Ethnopharmacological relevance: Selaginella tamariscina (P.Beauv.) Spring is a traditional medicinal plant used to treat various human diseases, including cancer, in Asia. The detailed molecular mechanism underlying the anti-cancer effects of this plant and the anti-cancer action of the combinatorial treatment of S. tamariscina and doxorubicin have not yet been investigated. Aim of the study: We evaluated the inhibitory activity of S. tamariscina extract (STE) and its major compound, amentoflavone, on human aldo-keto reductase family 1B10 (AKR1B10), which is a detoxification enzyme involved in drug resistance, to evaluate their anti-cancer effects and their potential as adjuvant agents for doxorubicin cancer chemotherapy. Materials and methods: We tested the AKR1B10 inhibitory activity of STE and amentoflavone via an in vitro biochemical assay using recombinant human AKR1B10. We tested the anti-proliferative activity in A549, NCI-H460, SKOV-3, and MCF-7 human cancer cells, which contain different expression levels of AKR1B10, and determined the combination index to evaluate whether the addition of STE and amentoflavone is synergistic or antagonistic to the anti-cancer action of doxorubicin. We finally evaluated the in vivo anti-tumor effects of STE in a nude mouse xenograft model of A549 cells. Results: STE and amentoflavone potently inhibited human AKR1B10 and synergistically increased the doxorubicin anti-proliferative effect in A549 and NCI-H460 human lung cancer cells that express a high level of AKR1B10 mRNA and protein. STE also significantly inhibited A549 tumor growth in animal experiments. Conclusion: Our results suggest that STE and amentoflavone could be potential anti-cancer agents that target AKR1B10 and might be candidate adjuvant agents to boost the anti-cancer effect of doxorubicin. Graphical abstract: